ROLE PLAYING STRATEGY IN ENHANCING STUDENTS’ IDIOMATIC EXPRESSION MASTERY - Prayuda, Meikardo Samuel; Tarigan, Karisma Erikson (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2024)
This research discussed about the use of Role Playing Strategy in enhancing students’ Idiomatic Expression Mastery. This research was conducted to the grade X students of SMA SWASTA PKMI EFESUS AEK BATU. This research was conducted in Classroom Action Research in order to find out how the process of Role Playing Strategy enhanced the students’ Idiomatic Expression Mastery. From this research, it was found out that the implementation of the first cycle was last well but less condusive. The students mean score in the theoretical test was 62.57 while in practical test was 28.57. The result had not fulfilled the requirement so the second cycle need to be conducted. 4. Based on the next findings, the problems had already been fixed and the students’ mastery in learning was also improved. It can be seen from the students’ score in the theoretical test with the mean 80.00, while in the practical test was 85.71. The qualitative data showed positive improvement from cycle one to cycle two. It was found out that students were interested in learning by using role playing strategy. Therefore, it was concluded that teaching by using role playing was effective in improving the students’ idiomatic expression mastery.